URANG BANJAR: TOLAK-TARIK DEMOKRASI DAN KEBUDAYAANNYA - M. Rifqinizamy Karsayuda (Universitas Andalas, 2017)
There are no general solutions to the problem of culturally divided countries. Every solutions will need to be costum tailored the features of each country. (Robert A Dahl)